Perception of Urban Quality of Life in Residents of the Metropolitan Area of Monterrey, Mexico: Psychoeducational Importance - García-Luna Romero, Ana C. (2022)
Urban sprawl is a phenomenon of great importance for people who live in large cities and feel the effects of it, which can affect their quality of life. In this regard, the objective of this research is to know the perception of the urban being in relation to the quality of urban life in the metropolitan area of Monterrey, Mexico. A qualitative investigation was carried out, of thematic analysis design. 24 residents of the metropolitan area of Monterrey participated. A semi-structured in-depth interview was applied. As results, it was found that the quality of urban life can be understood through external qualities, such as the standard of living appropriate to their needs; and internal, such as urban happiness, urban lifestyles and rethinking the link between society and nature. It is concluded that both the perception of external and internal qualities affect the quality of urban life. Likewise, their knowledge is important for the formulation of psychoeducational interventions that improve the quality of urban life in residents.